The Impact of Social and Ecological Factors on Coupled Human-Environment Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The relationship between human beings and the ecological environment poses a significant global challenge for the present and the future. As human–environment interactions become more complex, it is essential to measure and understand the spatiotemporal dynamics of coupled human–environment systems and how they are influenced by social and ecological factors. This reprint offers twenty original research articles that explore the latest developments in monitoring and projecting the spatiotemporal changes of the coupled system, examining the responses of the coupled system to socio-ecological drivers and processes, and discussing the implications for the sustainable management of the coupled system.